Conceptual, Legal, and Ethical Considerations in Physician-Assisted Suicide: An Overview - Ahmad, Nehaluddin; Masum, Ahmad; Ali, Aqilah Walin (UUM Press, 2024)
Physician-assisted suicide (PAS) remains a contentious and highly debated topic within medical, legal, and ethical spheres. The complex issue of (PAS) raises significant inquiries regarding patient autonomy and societal norms. Ambiguities in conceptual, legal, and ethical aspects impede policy formulation, leading to unequal access and apprehensions about patient welfare and confidence. This article provides a thorough examination of assisted suicide, exploring its legal, ethical, and medical dimensions. It aims to facilitate informed dialogue and stimulate further investigation into the legal framework and ethical considerations surrounding this contentious issue. Through a library-based research approach and qualitative analysis of existing literature, this study delves into the diverse facets of assisted suicide. The article begins with a definition and contextualisation of assisted suicide, distinguishing it from related end-of-life practices. It then delves into the legal landscape, discussing different legal frameworks and regulations across various jurisdictions, and significant legal cases that have shaped the current discourse. From an ethical standpoint, this article explores the ethical considerations involved in assisted suicide, including autonomy, dignity, and the sanctity of life, and presents the perspectives of different stakeholders. The medical perspective examines the role of healthcare professionals, the criteria for assisted suicide, and empirical research on its effectiveness and safety. Realworld case studies are presented to illustrate the complexities of assisted suicide. Furthermore, this article analyses public opinion and ongoing debates on the topic. Ultimately, this analysis aims to provide readers with a comprehensive understanding of assisted suicide, fostering informed discussions and encouraging further exploration of this contentious issue